READING ABBAS: A POSTCOLONIAL STUDY OF THE MAIN CHARACTER OF KELAS INTERNASIONAL - Fatahillah, Anggun Putri (2017)
Kelas Internasional, an Indonesian TV series depicting the dynamics of a class consisting of students of different nationalities, has a Nigerian character named Abbas, who is the only African student in the story. It is quite uncommon in Indonesian films to have an African playing as the main character; this study thus aims to analyze how the African character Abbas is represented in the TV series Kelas International. Adopting a qualitative descriptive method, the study draws on Hall's (1997) theory of representation, Said's (1979) Orientalism, and Doh's (2009) stereotyping Africa to delve into the representations of Abbas. The study also employs Heintz and Stracey's (2008) film theory, focusing primarily on the elements of mise en scène and the soundtracks, to understand how the representation of Abbas is constructed through film elements. The data analysis reveals that the character Abbas is primarily represented in a negative light: being educationally backward, economically poor, and attitude-wise impolite. This study indicates that Kelas Internasional tends to perpetuate negative stereotypes about Africans, rather than counter them. This study is expected to not only contribute to the field of postcolonial studies, but more importantly to raise Indonesian people's critical awareness of implicit messages embedded in literary works. ;--- Kelas Internasional, salah satu serial TV Indonesia, yang menceritakan tentang situasi suatu kelas yang berisi murid-murid dari berbagai negara, mempunyai satu karakter yang berasal dari Nigeria bernama Abbas, yang juga merupakan satu-satunya murid yang berasal dari Afrika. Keberadaan karakter seorang Afrika di dalam dunia perfilman Indonesia dirasa sangat jarang; maka dari itu penelitian ini bertujuan untuk menganalisa bagaimana suatu karakter dari Afrika yang bernama Abbas direpresentasikan di dalam serial TV Kelas Internasional. Dengan menggunakan metode deskriptif kualitatif, kajian ini menggunakan teori representasi milik Hall (1997), teori Orientalism oleh Said (1979), dan teori stereotyping Africa oleh Doh (2009) untuk menelaah representasi Abbas dalam film. Kajian ini juga menggunakan teori film milik Heintz dan Stracey yang secara spesifik berfokus kepada elemen mise en scène dan the soundtracks, untuk memahami bagaimana representasi Abbas dikonstruksi melalui elemen-elemen film tersebut. Analisis data menunjukan bahwa karakter Abbas direpresentasikan secara negatif: terbelakang dalam pendidikan, miskin, dan tidak sopan. Kajian ini menunjukan bahwa Kelas Internasional cenderung melanggengkan stereotipe negatif mengenai orang-orang Afrika, daripada menguranginya. Kajian ini diharapkan dapat tidak hanya berkontribusi pada bidang kajian pasca-penjajahan, namun lebih pentingnya lagi untuk meningkatkan kesadaran berpikir kritis orang Indonesia terhadap pesan-pesan implisit yang terdapat dalam karya sastra.